Hemostatic Management after Tooth Extraction in Patients under Ongoing Antithrombotic Therapy - Minagi, Shogo; Toyota, Masahito (Ronen Shika Igaku, 2012)
The purpose of this study was to investigate postoperativebleedingfor tooth extraction in patients maintained on oral antithrombotic therapy. The subjects were 41 patients who came to the Kasaoka Hospital from April 2009 to December 2010, including15 receiving warfarin alone, 7 receiving warfarin with additional antiplatelet drugs, and 19 receivingantiplatelet drugs alone. A total of 157 teeth were extracted on 94 occasions. All teeth were extracted without reducingthe usual antithrombotic therapy, andagelatin sponge was applied and suturing was performed for local hemostasis. Postoperative hemorrhage occurred in only 2 of 94 occasions of tooth extractions; one case was with warfarin alone and the other case was with warfarin and additional antiplatelet drugs. In both cases, local hemostatic methods, biting downongauze for compression and applyingsprint for hemostasis, were successful in 30 minutes when postoperative hemorrhage occured. Serious thromboembolisms includingfatal cases have been previously reported in 1% cases when tooth extraction was enforced with discontinuinganticoagulant therapy. Therefore, tooth extraction under the condition of continuing oral antithrombotic therapy was recommended by the guideline of the Japanese Circulation Society in 2004. However, accordingto a survey in 2007, many physicians and dentists still reduced or stopped temporarily anticoagulant or antiplatelet drugs in spite of the guideline. We considered it important to sensitize both medicine and dentistry professionals to the importance of appropriate dental treatment for elderly people with antithrombotic therapy, whose numbers are increasingin Japan.